N-Acetyl-l-cysteine and aminooxyacetic acid differentially modulate trichloroethylene reproductive toxicity via metabolism in Wistar rats - Su, Anthony L. (Arch Toxicol, 2021)
Exposure to the industrial solvent trichloroethylene (TCE) has been associated with adverse pregnancy outcomes in humans and decreased fetal weight in rats. TCE kidney toxicity can occur through formation of reactive metabolites via its glutathione (GSH) conjugation metabolic pathway, largely unstudied in the context of pregnancy. To investigate the contribution of the GSH conjugation pathway and oxidative stress to TCE toxicity during pregnancy, we exposed rats orally to 480 mg TCE/kg/day from gestational day (GD) 6 to GD 16 with and without N-acetyl-l-cysteine (NAC) at 200 mg/kg/day or aminooxyacetic acid (AOAA) at 20 mg/kg/day as pre/co-treatments from GD 5–16. NAC is a reactive oxygen species scavenger that modifies the GSH conjugation pathway, and AOAA is an inhibitor of cysteine conjugate β-lyase (CCBL) in the GSH conjugation pathway. TCE decreased fetal weight, and this was prevented by AOAA but not NAC pre/co-treatment to TCE. Although AOAA inhibited CCBL activity in maternal kidney, it did not inhibit CCBL activity in maternal liver and placenta, suggesting that AOAA prevention of TCE-induced decreased fetal weight was due to CCBL activity inhibition in the kidneys but not liver or placenta. Unexpectedly, NAC pre/co-treatment with TCE, relative to TCE treatment alone, altered placental morphology consistent with delayed developmental phenotype. Immunohistochemical staining revealed that the decidua basale, relative to basal and labyrinth zones, expressed the highest abundance of CCBL1, flavin-containing monooxygenase 3, and cleaved caspase-3. Together, the findings show the differential effects of NAC and AOAA on TCE-induced pregnancy outcomes are likely attributable to TCE metabolism modulation.